Leptin and Nutritional Markers in Childhood Protein-Energy Malnutrition - ERBAGCI*, A.B.; KILINÇ†, M.; TARAKÇIOGLU, M.; TAYSI, S.; KOCABAS, R. (Asian Journal of Chemistry, 2009)
Leptin is an important signal in metabolic/endocrine adaptation toprolonged nutritional deprivation. This cross-sectional study was performedto determine alterations associated with protein-energy malnutritionin serum levels of leptin and classical nutritional markers. Forty-twochildren with protein-energy malnutrition was classified according toGomez and 21 healthy controls were recruited. Serum leptin, albumin,prealbumin, fibronectin, transferrin, lipoprotein (a) and whole bloodhemoglobin concentrations were determined. Leptin levels were significantlylower in undernourished children, declining with degree ofmalnutrition. Alteration of albumin, hemoglobin and lipoprotein (a)became apparent at late stages of malnutrition. Gomez classificationwas the only significant contributor to the variations in leptin concentrationsamong age, weight, presence of infection, breast-feeding durationand age at feeding with complementary foods. This study provides evidencethat leptin is sensitive to stages of malnutrition independent of bodyweight, probably for it's role in metabolic adaptation. Serum prealbumin,transferrin and fibronectin does not offer a sensitive alternative in thebackground of increased susceptibility to infection.